Inheritance of Resistance to Papaya Ringspot Virus-Papaya Strain in Melon (Cucumis melo L.) - Budi Setiadi Daryono; Keiko T. Natsuaki` (Universitas Gadjah Mada, 2006)
Papaya ringspot virus (PRSV) is one of potyviruses causing severe damage to the production of cucurbit crops including melon, however resistant melons to PRSV have not yet commercially available. To find resistant genetic source of melons against PRSV, sixty three melons were manually inoculated with PRSV-papaya strain (PRSV-P) isolated in Thailand. Levels of resistance to PRSV-P accumulation in melon leaf tissue were evaluated using a combination of visual symptom observation and RT-PCR analysis. Among melons tested, Yamatouri, Mawatauri, PI 414723, and PI 371795 showed to be resistance to PRSV-P To study the inheritance of resistance to PRSV-P, breeding experiments were conducted by crossing the resistant Yamatouri with susceptible Vakharman. The genetic analysis results revealed that a single dominant gene conferred resistance to PRSV-P in Yamatouri and its generation.